Hesitant avoidance while walking: an error of social behavior generated by mutual interaction - Honma, Motoyasu; Koyama, Shinichi; Kawamura, Mitsuru (Frontiers in Psychology, 2015)
Altering physical actions when responding to changing environmental demands is important but not always effectively performed. This ineffectiveness, which is an error of social behavior generated by mutual interactions, is not well understood. This study investigated mechanisms of a hesitant behavior that occurs in people walking toward each other, causing people to move in the same direction when attempting to avoid a collision. Using a motion capture device affixed to 17 pairs, we first confirmed the hesitant behavior by a difference between the experimental task, which involved an indeterminate situation to assess the actions of another individual, and the control task, which involved a predetermined avoiding direction, in a real-time situation involving two people. We next investigated the effect of three external factors: long distance until an event, synchronized walking cycle, and different foot relations in dyads on the hesitant behavior. A dramatic increase in freezing and near-collision behavior occurred in dyads for which the avoiding direction was not predetermined. The behavior related with the combination of long distance until an event, synchronized walking cycle, and different foot relations in dyads. We found that the hesitant behavior is influenced by an interpersonal relationship under enough distance to predict other movement. The hesitant behavior has possibly emerged as an undesired by-product of joint action. These results contribute to our understanding of the mechanisms of adaptive control of perception-action coupling in mutual interaction.